The Role of Visum et Repertum and Clinical Examination in Sexual Violence Cases: A Literature Review - Muhammad Luthfi Adnan; Niufti Ayu Dewi Mahila; Syamsu Tatang Triyuwanto (Universitas Udayana, 2024)
Background: Physical examination of victims of sexual violence is required for the preparation of a visum et repertum as evidence in trial. This review aims to discuss the role of Visum et Repertum and clinical examination of victims who have experienced sexual violence. Method: The literature search was carried out through an electronic search engine with keywords related to the purpose of the review. Discussion: Visum et Repertum is one of the pieces of evidence to reveal the incidence of sexual violence experienced by the victim. In handling cases of sexual violence, a doctor must understand his role as a medical professional to help disclose cases. Physicians must carry out the necessary clinical examinations to be able to interpret their findings into the Visum et Repertum requested by the police. Also, a physician has a role to help the patient's recovery by providing treatment so that the victim can recover from the trauma experienced by the victim due to sexual violence. Understanding the role of physicians in handling cases of sexual violence can help many parties to reveal cases of sexual violence and reduce the burden on sexual violence victims.